School Climate and Mathematical Disposition of Grade 10 Students - Mariva Colita; Rinante L. Genuba (International Journal of Trends in Mathematics Education Research, 2019)
The purpose of this study was to determine which domain of school climate best influences mathematical dispositions of Grade 10 students. Universal sampling technique was used in this study wherein 118 Grade 10 students from the private secondary schools in Barangay Ilang, Davao City, were chosen as the participants. By utilizing a non-experimental quantitative research design, specifically, correlational technique, through the use of a validated questionnaire, mean, Pearson r and regression techniques, it was revealed that the level of school climate of the private secondary schools were high. In the same way, the level of the mathematical dispositions of the Grade 10 students was also high. In addition, it was found out that school climate and mathe-matical dispositions of the students were significantly and positively related with an r-value of 0.490 and p-value less than 0.05. Findings further revealed that among the four domains of school climate, it was expectations that best influenced the dispositions of the students towards mathematics.